Mentoring and Literacy on the Use of a Chlorophyll Measurement Device for Farmers in Sumbersari Village, Bandung District - Erwani Merry Sartika; Daniel Setiadikarunia; Audyati Gany; Aan Darmawan; Herawati Yusuf; Heri Andrianto; Jimmy Gozali; Novie Theresia BR. Pasaribu; Yulianti Talar; Arvin Ezekiel Denri Utama; Giri Shaffaat AL Muttaqin; Annisa Maizano; Wulan Sallydri Santoso (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
Farmers in Sumbersari village, located in Bandung district, were in great need of assistance in effectively managing their paddy fields to ensure the production of high quality and high yield rice. One crucial factor that significantly impacts it is the proper application of urea fertilizer based on the conditions of the paddy plants, which can be determined by measuring the chlorophyll content present in the leaves of paddy plants. Therefore, mentoring and literacy activities were held to educate farmers on the utilization of a chlorophyll content measuring device which is the result of research previously conducted by the Faculty of Engineering, Universitas Kristen Maranatha so that farmers are able to measure the precise amount of fertilizer that must be applied in accordance to the needs of their paddy plants. The mentoring methods covered socialization, demonstration, and hand-on practice with the measuring device. As the result, all farmers became proficient in using the measuring device that had previously been developed. The device’s size and weight are appropriately designed making it convenient for farmers to carry the device the fields and measure the chlorophyll content in the leaves of paddy plants.